Balanceamento de Tráfego entre Servidores de Vídeo MPEG-DASH em Redes Definidas por Software - dos Passos, Edenilson Jônatas; Fiorese, Adriano (Anais do Workshop de Gerência e Operação de Redes e Serviços (WGRS), 2019)
With popularization of video streaming service in recent years, new video distribution technologies have been created. Currently, one of the most promising ones is the Moving Picture Expert Group Dynamic Adaptive Streaming over HTTP or MPEG-DASH. However, with the limitation of the TCP/IP network structure, the end user quality of experience may be affected. This is due to several factors such as network congestion, bandwidth limitation, non-optimal choice of a content provider server and server overload. This article presents a load-balancing solution between MPEG-DASH video servers based on Software Defined Networks, using as a balancing metric the throughput of the content server.